Limitations of Current Therapeutic Options, Possible Drug Targets and Scope of Natural Products in Control of Leishmaniasis - Tiwari, Neeraj; Gedda, Mallikarjuna R.; Tiwari, Vinod K.; Singh, Surya P.; Singh, Rakesh K. (Mini Reviews in Medicinal Chemistry, 2018)
Soon after the identification of Leishmania parasite as a causative agent, the pentavalent antimony compounds have been the mainstay to treat all forms of leishmaniasis. Due to growing incidences of antimony resistant parasites and unavailability of true antileishmanial compounds, few drugs like pentamidine (antimicrobial), amphotericin B (antifungal) or miltefosine (antitumor) are currently being used but these are associated with serious side effects. Unfortunately, the emergence of amphotericin B and miltefosine resistant parasites in clinical settings has further questioned their sustained use in leishmanial control. Moreover, the parameters of protective immunity are not well understood in leishmanial pathogenesis therefore, a vaccine candidate, either prophylactic or preventive, is still an unrealized goal. In addition, the emergence of insecticide resistance sand flies in disease endemic regions also stance a big threat for the current elimination strategies. Therefore, in lieu of the limited drug regimen and unavailability of a vaccine, the necessity of a true antileishmanial agent is always there. Although, leishmanial infections have been neglected for many decades but recent studies have identified potential drug targets that could be targeted to control the growth of parasites. In recent past many compounds derived from natural sources have also been shown to possess excellent antiparasitic potential; however, most of these studies are limited to primary evaluation and only a few have reached to clinical levels. In this review, we discuss the limitations of current drug regimen, explore possible drug targets of Leishmania species and summarize wide range of compounds isolated from various natural sources that are worth screening as antileishmanial drug candidates.
Keywords: Antileishmanial compounds